Tahlil Rasail al-Da’wah fi Mawaadd al-Ta’lim al-Raqmiyah li Maharah al-Qiraah ‘ala Asaasi Maharah al-Tafkir al-Ulya li al-Mustawa al-Jami’i: تحليل رسائل الدعوة في مواد التعليم الرقمية لمهارة القراءة على أساس مهارات التفكير العليا للمستوى الجامعي - Permata, Icha Gilang; Annida, Alfika Syafa; Mardiyah, Tika (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
In the modern era, technology and communication are developing rapidly and provide teens with an easy way to gain bad influence from various sources. This makes them suffer from serious moral degradation. Especially for students in Arabic language education as potential teachers in religious institutions. So they should be nurtured by introducing advocacy messages in the learning process. The digital teaching materials entitled